FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP ISLAMIC SOCIAL REPORTING PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA TAHUN 2019-2021 - Asfa Haimana Faisyar; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2023)
This study aims to examine various factor that may affect Islamic Social Reporting (ISR). Specifically, four factors are chosen as the independent variables, namely firm size, profitability, firm age, and independent commissioner. ISR as the dependent variable of this study is measured by ISR Index using content analysis method. The population of this study are consumer non-cyclical companies registered at Indeks Saham Syariah Indonesia (ISSI) from 2019 to 2021. The total sample obtained is 26 companies that is determined using purposive sampling method with numerous criteria. The analytical method used for this study is multiple linear regression.The result of this study indicates that firm size, profitability, and firm age have a significant positive influence on ISR. Meanwhile, independent commissioner has no significant effect on ISR.